Expression and phylogenetic analysis of the zic gene family in the evolution and development of metazoans - Layden Michael J; Meyer Néva P; Pang Kevin; Seaver Elaine C; Martindale Mark Q (EvoDevo, 2010)
Abstract Background zic genes are members of the gli/glis/nkl/zic super-family of C2H2 zinc finger (ZF) transcription factors. Homologs of the zic family have been implicated in patterning neural and mesodermal tissues in bilaterians. Prior to this study, the origin of the metazoan zic gene family was unknown and expression of zic gene homologs during the development of early branching metazoans had not been investigated. Results Phylogenetic analyses of novel zic candidate genes identified a definitive zic homolog in the placozoan Trichoplax adhaerens, two gli/glis/nkl-like genes in the ctenophore Mnemiopsis leidyi, confirmed the presence of three gli/glis/nkl-like genes in Porifera, and confirmed the five previously identified zic genes in the cnidarian Nematostella vectensis. In the cnidarian N. vectensis, zic homologs are expressed in ectoderm and the gastrodermis (a bifunctional endomesoderm), in presumptive and developing tentacles, and in oral and sensory apical tuft ectoderm. The Capitella teleta zic homolog (Ct-zic) is detectable in a subset of the developing nervous system, the foregut, and the mesoderm associated with the segmentally repeated chaetae. Lastly, expression of gli and glis homologs in Mnemiopsis. leidyi is detected exclusively in neural cells in floor of the apical organ. Conclusions Based on our analyses, we propose that the zic gene family arose in the common ancestor of the Placozoa, Cnidaria and Bilateria from a gli/glis/nkl-like gene and that both ZOC and ZF-NC domains evolved prior to cnidarian-bilaterian divergence. We also conclude that zic expression in neural ectoderm and developing neurons is pervasive throughout the Metazoa and likely evolved from neural expression of an ancestral gli/glis/nkl/zic gene. zic expression in bilaterian mesoderm may be related to the expression in the gastrodermis of a cnidarian-bilaterian common ancestor.